Association between serum vitamin D levels and subclinical coronary atherosclerosis and plaque burden/composition in young adult population - Satilmis, Seckin; Celik, Omer; Biyik, Ismail; Ozturk, Derya; Celik, Kubra Asik; Akin, Fatih; Ayca, Burak; Yalcin, Burce; Dagdelen, Sinan (ASSOC BASIC MEDICAL SCI FEDERATION BOSNIA \& HERZEGOVINA SARAJEVO, 2015)
Evidence suggests that low 25-OH vitamin D (25)(OH)D concentrations may increase the risk of several cardiovascular diseases such as hypertension, peripheral vascular disease, diabetes mellitus, obesity, myocardial infarction, heart failure and cardiovascular mortality. Recent studies suggested a possible relationship between vitamin I) deficiency and increased carotid intima-media wall thickness and vascular calcification. We hypothesized that low 25(OH)D may be associated with coronary atherosclerosis and coronary plaque burden and composition, and investigated the relationship between serum vitamin I) levels and coronary atherosclerosis, plaque burden or structure, in young adult patients by using dual-source 128x2 slice coronary computed tomography angiography (CCTA). We included 98 patients with coronary atherosclerosis and 110, age and gender matched, subjects with normal findings on CCTA examinations. Patients with subclinical atherosclerosis had significantly higher serum total cholesterol, triglycerides, hs-CRP, uric acid, HbA1c and creatinine levels and lower serum 25(OH)l) levels in comparison with controls. There was no significant correlation between 25(OH)D and plaque morphology. There was also a positive relationship between 25(OH)D and plaque burden of coronary atherosclerosis. In multivariate analysis, coronary atherosclerosis was associated high hs-CRP (adjusted OR: 2.832), uric acid (adjusted OR: 3.671) and low 25(OH)D (adjusted OR: 0.689). Low levels of 25(OH)D were associated with coronary atherosclerosis and plaque burden, but there was no significant correlation between 25(OH)D and plaque morphology.
Keywords: vitamin D; coronary atherosclerosis; uric acid; hs-CRP